2011
DOI: 10.1007/s11999-010-1673-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural Allograft as an Option for Treating Infected Hip Arthroplasty with Massive Bone Loss

Abstract: Background Revision of the infected hip arthroplasty with major bone loss is difficult. Attempts to restore bone stock with structural allograft are controversial. Questions/purposes We assessed the (1) reinfection rate; (2) rerevision rate; (3) radiographic graft union, resorption, and implant migration; (4) Harris hip scores at 1 year and at last followup compared with before surgery; and (5) other major complications associated with the use of bulk structural allograft to treat massive bone loss in infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 37 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…Synthetic models have favored a direct exchange approach [34]; however, pooled clinical data have demonstrated the superiority of the two-stage protocol over a period of decades [7,15]. A staged protocol has been applied with control of infection in the setting of massive bone loss [16], resistant organisms [17], and when used with oral [3] and abbreviated courses of intravenous antibiotics [33]. The use of high-dose antibiotic-laden cement spacers for the first-stage operation has yielded infection control rates superior to those with resection arthroplasty alone [2]; although this has not been a uniformly consistent finding [26,30], it is the most commonly reported approach.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic models have favored a direct exchange approach [34]; however, pooled clinical data have demonstrated the superiority of the two-stage protocol over a period of decades [7,15]. A staged protocol has been applied with control of infection in the setting of massive bone loss [16], resistant organisms [17], and when used with oral [3] and abbreviated courses of intravenous antibiotics [33]. The use of high-dose antibiotic-laden cement spacers for the first-stage operation has yielded infection control rates superior to those with resection arthroplasty alone [2]; although this has not been a uniformly consistent finding [26,30], it is the most commonly reported approach.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 The use of structural allografts provides adequate support and transforms uncontained acetabular defects to contained ones and achieves satisfactory outcome, 7,8,20,30 with a revision rate of up to 7% at 10 years. 31 Nonetheless, poor midto-long-term outcome has also been reported, with revision rates ranging from 33 to 60%. 3,32,33 To improve outcome, adding bone substitute material to the allograft 34 and supercharging the structural allografts with mesenchymal stem cells 35 have been proposed.…”
Section: Methodsmentioning
confidence: 99%
“…Radiographic evaluation of graft integration is prone to interobserver error 31 and overestimation. 37 Radiography tends to magnify the extent of host-graft healing and incorporation at the interface.…”
Section: Methodsmentioning
confidence: 99%
“…Richards et al 33 reported good success with a novel technique that uses an antibiotic cement-loaded Küntscher nail cemented with a highly polished femoral stem as a temporary spacer in the setting of massive femoral bone loss. 34 Infected periprosthetic fractures represent a combination of two entities that each present a unique set of challenges. 34 Infected periprosthetic fractures represent a combination of two entities that each present a unique set of challenges.…”
Section: Special Considerations For Challenging Casesmentioning
confidence: 99%